An Assessment of Forest Tenure in Myanmar : Securing Forest Tenure for Sustainable Livelihoods - World Bank (World Bank, Washington, DC, 2020)
Forests are an important economic and social resource, critical to the culture and livelihood of communities across Myanmar. Forest resources are key secondary income sources for more than half the rural population, and close to two-thirds of rural energy demands are met by traditional forest fuels. Hence, forest-dependent rural communities need secure access and use rights to forestland and resources. Building on several ongoing reform measures and public consultations, this assessment is being undertaken by the Forest Department (FD) of the Ministry of Natural Resources and Environmental Conservation (MoNREC) to contribute to debates on forest tenure in Myanmar and is financed by the World Bank office in Yangon. It will also serve as input for the government’s policy reforms and its national strategy on rural development engagement within the context of forest tenure. The overall goal of this assessment is to outline an improved approach and policy roadmap to strengthen forest tenure. This will enable enhanced government interventions, better services, improved risk-management in rural development, and better livelihoods for forest-dependent rural communities. It is being undertaken within the global framework and international principles on forest tenure and governance. The assessment was carried out between September 2019 and January 2020.